Subjetivação e liberdade em Michel Foucault - Santos, Alexandre Gomes dos (2011)
The works of Michel Foucault, as he says at the end of his life, had as the thematic axis the debate about the forms of subjectivation experienced by individuals in Western society and its relationship with the “truth games”, or what is said true or false through the discourses of knowledge about man. Our attempt had been to apprehend this unrestrained relationship between subject and truth from a theme that is related to us – freedom. Freedom as the “ontological condition of ethics”, an ethic that is presented as the reflected form that freedom takes. It is from this status that we inquire the Foucaultian discourse, pursuing the notion of “care of self”, a self that presents itself while it promotes itself, which causes to us some confusion when we percept the lack of content of this self, only having the form that the subject gives to himself while making himself existing and active in the world. Foucault provides us with a method where the foundation, the universal, where the given and unquestioned concept is set aside operating the and if formula. And if we had no universals to ensure our knowledge, and if we only thought about the subjects as realities resulting from the effects that certain concepts promote when made worth as the human realities? This method we embrace here in order to get rid of thinking basted in the logic of the universal basis, then going to require the new in the thought, arming us with your present. The freedom in Foucault is a theme that was offered to us while we caught a glimpse in different perspectives of that subject-truth relation that Foucault pursued as a archaeological thinker of knowledges about the human, as a genealogical thinker of the powers coupled to such knowledges, and as a thinker of an ethics that takes care of the other by a care of self.